Advanced Therapeutic Gastrointestinal Endoscopy in Children - Today and Tomorrow - Zaheer Nabi; Duvvur Nageshwar Reddy (Korean Society of Gastrointestinal Endoscopy, 2018)
Gastrointestinal (GI) endoscopy plays an indispensable role in the diagnosis and management of various pediatric GI disorders. While the pace of development of pediatric GI endoscopy has increased over the years, it remains sluggish compared to the advancements in GI endoscopic interventions available in adults. The predominant reasons that explain this observation include lack of formal training courses in advanced pediatric GI interventions, economic constraints in establishing a pediatric endoscopy unit, and unavailability of pediatric-specific devices and accessories. However, the situation is changing and more pediatric GI specialists are now performing complex GI procedures such as endoscopic retrograde cholangiopancreatography and endoscopic ultrasonography for various pancreatico-biliary diseases and more recently, per-oral endoscopic myotomy for achalasia cardia. Endoscopic procedures are associated with reduced morbidity and mortality compared to open surgery for GI disorders. Notable examples include chronic pancreatitis, pancreatic fluid collections, various biliary diseases, and achalasia cardia for which previously open surgery was the treatment modality of choice. A solid body of evidence supports the safety and efficacy of endoscopic management in adults. However, additions continue to be made to literature describing the pediatric population. An important consideration in children includes size of children, which in turn determines the selection of endoscopes and type of sedation that can be used for the procedure.